A2 Milk and BCM-7 Peptide as Emerging Parameters of Milk Quality - Giribaldi, Marzia; Lamberti, Cristina; Cirrincione, Simona; Giuffrida, Maria Gabriella; Cavallarin, Laura (Frontiers in Nutrition, 2022)
Beta-casein makes up about 30 % of the total protein contained in milk and can be present in cows’ milk in two distinct forms (A1 or A2) or as a combination of the two. The only difference between these two variants of β-casein (β-CN) is a single amino acid substitution. This results in a different behavior of the protein upon enzymatic cleavage, following human consumption or due to microbial action. In most of the commercially available milk containing A1 or A1/A2 β-CN variants, the β-casomorphin-7 peptide (BCM-7) is released upon digestion and during cheese manufacturing/ripening, while this does not happen with A2 milk. BCM-7 is a known μ-opioid receptor agonist that may influence the gastro-intestinal physiology directly and may also exert effects elsewhere in the body, such as on the cardiovascular, neurological and endocrine systems. The present article is aimed at a revision of prior review papers on the topic, with a focus on the impact of ingestion of A1 β-CN milk and A2 β-CN milk on any health-related outcomes and on the impact of A1 or A2 β-CN variant on technological properties of cows’milk. When systematic reviews were considered, it was possible to conclude that A2 β-CN exerts beneficial effects at the gastrointestinal level compared with A1 β-CN, but that there is no evidence of A1 β-CN having negative effects on human health. Physicochemical differences among cows’ milk containing either β-CN A2 or β-CN A1 and their effects on technological properties are discussed.